Phosphorus and zinc uptake efficiency of potato (Solanum tuberosum) in comparison to wheat (Triticum aestivum), maize (Zea mays) and sunflower (Helianthus annuus) - TREHAN, S P; SHARMA, R C (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1997 and 1998 to find out the plant parameters responsible for differential phosphorus and zinc uptake efficiency in potatoSolanum tuberosum L.), wheat (Triticum aestivum L. emend. Fiori & Paol.). maize (Zea mays L.) and sunflower (Helianthus annuus L.). Relative shoot dry weight without phosphorus expressed as per cent of shoot dry weight with phosphorus application was 38, 16 and 19% for potato, wheat and sunflower respectively. This showed that potato was more phosphorus efficient than wheat and sunflower. In the absence of phosphorus, the influx of phosphorus in potato was 13.5 (10-15 mol/s/cm) which was three times more than wheat and about two times more than sunflower. Relative shoot dry-matter yield without zinc expressed as per cent of yield with adequate zinc was 64, 57 and 130% for potato, maize and sunflower respectively indicating that sunflower was most zinc efficient plant. The phosphorus and zinc uptake efficiency of plants were positively related to their nutrient influxes but not with root/shoot ratio of the plant species.